Evaluation of Different Dental Materials Used in Forensic Dentistry: A Comparative Study - Arshdeep S. Kohli; Ganaraj Shetty; Hari P. Gone; Joseph J. K. Pothanikat; Neeta J. Pothanikat; Ahmed Al-Emam; Rahul Tiwari (Journal of Pharmacy and Bioallied Sciences)
Background: Forensic dentistry plays a pivotal role in the identification of individuals, particularly in mass disasters and criminal investigations. This study evaluates various dental materials used in forensic identification. Methods: Different dental materials were assessed for their effectiveness in forensic applications. Samples included dental amalgam, composite resins, glass ionomer cements, and dental ceramics. Parameters such as durability, ease of identification under forensic conditions, and resistance to environmental factors were analyzed. Results: Dental ceramics exhibited the highest durability and resistance to environmental degradation, followed by dental amalgam. Composite resins and glass ionomer cements showed lower performance in forensic conditions. Conclusion: Dental ceramics and amalgam provide superior forensic identification capabilities compared to other materials. This study supports the use of these materials in forensic dentistry due to their robustness and reliability.